MRI-guided prostate adaptive radiotherapy – A systematic review. Issue 3 (June 2016) - McPartlin, A.J.; Li, X.A.; Kershaw, L.E.; Heide, U.; Kerkmeijer, L.; Lawton, C.; Mahmood, U.; Pos, F.; van As, N.; van Herk, M.; Vesprini, D.; van der Voort van Zyp, J.; et al.
Abstract: Dose escalated radiotherapy improves outcomes for men with prostate cancer. A plateau for benefit from dose escalation using EBRT may not have been reached for some patients with higher risk disease. The use of increasingly conformal techniques, such as step and shoot IMRT or more recently VMAT, has allowed treatment intensification to be achieved whilst minimising associated increases in toxicity to surrounding normal structures. To support further safe dose escalation, the uncertainties in the treatment target position will need be minimised using optimal planning and image-guided radiotherapy (IGRT). In particular the increasing usage of profoundly hypo-fractionated stereotactic therapy is predicated on the ability to confidently direct treatment precisely to the intended target for the duration of each treatment. This article reviews published studies on the influences of varies types of motion on daily prostate position and how these may be mitigated to improve IGRT in future. In particular the role that MRI has played in the generation of data is discussed and the potential role of the MR-Linac in next-generation IGRT is discussed.